Nutrition transition and the structure of global food demand - Gouel, Christophe; Guimbard, Houssein (International Food Policy Research Institute, 2017)
Estimating future demand for food is a critical aspect of global food security analyses. The process linking dietary changes to wealth is known as the nutrition transition and presents well-identified features that help to predict consumption changes in poor countries. This study proposes to represent the nutrition transition with a nonhomothetic, flexible-in-income, demand system, known as the Modified Implicitly Directly Additive Demand System (MAIDADS). The resulting model is transparent and estimated statistically based on cross-sectional information from FAOSTAT the statistical database of the Food and Agriculture Organization of the United Nations. It captures the main features of the nutrition transition: rise in demand for calories associated with income growth; diversification of diets away from starchy staples; and a large increase in caloric demand for animal-based products, fats, and sweeteners. The estimated model is used to project food demand between 2010 and 2050 based on a set of plausible futures (trend projections and Shared Socioeconomic Pathways scenarios). The main results of these projections are as follows: (1) global food demand will increase by 46 percent, less than half the growth in the previous four decades; (2) this growth will be attributable mainly to lower-middle-income and low-income countries; (3) the structure of global food demand will change over the period, with a 95 percent increase in demand for animal-based calories and a much smaller 18 percent increase in demand for starchy staples; and (4) the analysis of a range of population and income projections reveals important uncertainties depending on the scenario, the projected increases in demand for animal-based and vegetal-based calories range from 78 to 109 percent and from 20 to 42 percent, respectively.